Worship and Theology in England, Volume IV : From Newman to Martineau - Davies, Horton (Princeton, NJ : Princeton University Press, 2015)
In a rich survey encompassing music, art, literature, and architecture, Professor Davies studies the revolution in religious thought and worship in England during the Victorian era. One main trend, the return to conservatism, is revealed in the renascence of Roman Catholic worship, the Oxford Movement, and the search for traditional architecture and liturgy. This impetus was balanced by the drive toward innovation, through the Social Gospel, the Church's confrontation with science, and the new forms of worship sought by the Baptists, Congregationalists, and others. This is the fourth in a five-volume series.Originally published in 1962.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.
Frontmatter -- Acknowledgments -- Contents -- Illustrations -- Introduction -- Part One: The Appropriation of tradition -- I. The Renascence of Roman Catholic Worship: Winter and the "Second Spring" -- II. Ecclesiastical Architecture: from Grecian to Gothic -- III. Liturgical Renewal in the English Free Churches: A Survey -- IV. Presbyterian Worship, Scottish and English -- V. The Catholic Trend of Anglican Worship: The "Ritualistic" Controversy and the Religious Communities -- VI. New Forms of Primitivism -- VII. Faith Grappling with Doubt: The Theological Revolution -- VIII. The Liturgical Pioneers of the Older Dissent: Baptists and Congregationalists -- IX. The Newer Dissent: Methodism and Unitarianism -- X. The Power of the Victorian Pulpit -- Bibliography -- Index
Mode of access: Internet via World Wide Web.
In English.
Description based on online resource; title from PDF title page (publisher's Web site, viewed 08. Jul 2019)
Keywords: Public worship -- History; Theology, Doctrinal -- Great Britain -- History; Worship -- History; RELIGION / History